Elite Inclusiveness: The Case of Oxford - Zimdars, Anna (International Higher Education, 2010)
The University of Oxford can be used as a case study to illustrate three basic challenges faced in admitting undergraduates at highly selective universities: a normative (philosophical), empirical (social research), and policy level. The case of Oxford illustrates that universities are responsive to the social climate in which they operate. The undergraduate selection process can take into account the perceived wishes of government and society; achieving more inclusiveness in enrollment at selective universities is possible.